A review on medicinal properties of saffron toward major diseases - Abd Razak, Saiful Izwan; Hamzah, Mohd Syahir Anwar; Foong, Choi Yee; Abdul Kadir, Mohammed Rafiq; Mat Nayan, Nadirul Hasraf (Taylor & Francis, 2017)
The stigma of Crocus sativus, known as saffron, is one of the most expensive spices in the world. The bioactive components in saffron, picrocrocin, crocin, and safranal, have demonstrated a wide range of uses and capabilities in the medical field. This review is focused on the potential therapeutic applications of saffron on diabetes mellitus (DM), antitumor, anticancer, anti-depressant, Alzheimer’s disease (AD), cardiovascular disease (CVD), erectile dysfunction and antibacterial effects.